How to cheat at managing information security - Osborne, Mark.; Summitt, Paul M. (Rockland, MA : Syngress, 2006)
This is the only book that covers all the topics that any budding security manager needs to know! This book is written for managers responsible for IT/Security departments from mall office environments up to enterprise networks. These individuals do not need to know about every last bit and byte, but they need to have a solid understanding of all major, IT security issues to effectively manage their departments. This book is designed to cover both the basic concepts of security, non technical principle and practices of security and provides basic information about the technical details of many of the products - real products, not just theory. Written by a well known Chief Information Security Officer, this book gives the information security manager all the working knowledge needed to: Design the organization chart of his new security organization Design and implement policies and strategies Navigate his way through jargon filled meetings Understand the design flaws of his E-commerce and DMZ infrastructure * A clearly defined guide to designing the organization chart of a new security organization and how to implement policies and strategies * Navigate through jargon filled meetings with this handy aid * Provides information on understanding the design flaws of E-commerce and DMZ infrastructure.
The security organization -- The information security policy -- Jargon, principles, and concepts -- Information security laws and regulations -- Information security standards and audits -- Interview, bosses, and staff -- Infrastructure security -- Firewalls -- Intrusion detection systems : theory -- Intrusion detection systems : in practice -- Intrusion prevention and protection -- Network penetration testing -- Application security flaws and application testing.
Includes index.
Keywords: Computer security -- Management; Information technology -- Security measures; Electronic books